2019
DOI: 10.1017/dmp.2018.154
|View full text |Cite|
|
Sign up to set email alerts
|

Ethics and Floods: A Systematic Review

Abstract: Disaster ethics is a developing field of inquiry recognizing the wide variety of ethical issues confronting various professionals involved in planning for and responding to different types of disasters. This article explores how ethical issues related to floods are addressed in academic literature. The review involved analysis of publications on ethics and floods identified in a systematic literature search of electronic databases that included sociological, biomedical, and geophysical sources. The review meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
(212 reference statements)
0
4
0
Order By: Relevance
“…10 Mitrović et al revealed that in disaster situations, there are few practical guidelines or training. 56 Therefore, a study by Al Harthi recommended continuing education for nursing staff on ethical and legal issues. 16 The final theme is regarding the impact of ethical practices during a disaster.…”
Section: Discussionmentioning
confidence: 99%
“…10 Mitrović et al revealed that in disaster situations, there are few practical guidelines or training. 56 Therefore, a study by Al Harthi recommended continuing education for nursing staff on ethical and legal issues. 16 The final theme is regarding the impact of ethical practices during a disaster.…”
Section: Discussionmentioning
confidence: 99%
“…They include exemplifying the moral dilemmas encountered in flood protection (Morss & Wahl, 2007; Simonovic, 2011); the examination of equity from environmental justice to fair compensation (Eakin et al, 2021; Johnson et al, 2007; Kaufmann et al, 2018; Marks et al, 2020; Liao et al, 2019; O'Hare and White, 2018; Thaler & Hartmann, 2016; Thaler, 2021; Thaler et al, 2020; Walker & Burningham, 2011), and also to the fair distribution of flood risk (Doorn, 2018). More recently, the normative underpinnings of FRM (Ciullo et al, 2020), and the ethics of floods (Mitrović et al, 2019), have been broached. Taken as a whole, this literature has yet to focus on harm that could result from moral dilemmas experienced during flood events (Simonovic, 2011), or recognise outcome harm from deliberate floodings such as irreversible displacement and community loss (Liao et al, 2019), illnesses and even deaths (Marks et al, 2020; Shicutt & Asgarian, 2017).…”
Section: Literature Overview and Research Questionsmentioning
confidence: 99%
“…But as a nomenclature, “flood harm” is rarely used (see Mitrović et al, 2019: 822). Specific use of this nomenclature here requires justification.…”
Section: Introduction: the Normative Dimensions Of Flood Harm In Floo...mentioning
confidence: 99%
See 1 more Smart Citation